MDWA: a model-driven Web augmentation approach—coping with client- and server-side support - Urbieta, Mario Matías (2020)
Web augmentation is a set of techniques allowing users to define and execute software which is dependent on the presentation layer of a concrete Web page. Through the use of specialized Web augmentation artifacts, the end users may satisfy several kinds of requirements that were not considered by the analysts, developers and stakeholders that built the application. Although some augmentation approaches are contemplating a server-side counterpart (to support aspects such as collaboration or cross-browser session management), the augmentation artifacts are usually purely client-side. The server-side support increases the capabilities of the augmentations, since it may allow sharing information among users and devices. So far, this support is often defined and developed in an ad hoc way. Although it is clear that server-side support brings new possibilities, it is also true that developing and deploying server-side Web applications is a challenging task that end users hardly may handle. This work presents a novel approach for designing Web augmentation applications based on client-side and server-side components. We propose a model-driven approach that raises the abstraction level of both, client- and server-side developments. We provide a set of tools for designing the composition of the core application with new features on the back-end and the augmentation of pages in the front-end. The usability and the value of the produced augmentations have been evaluated through two experiments involving 30 people in total.